2009
DOI: 10.1603/008.102.0106
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and Range Expansion of North American Squash Bee, Peponapis Pruinosa (Apidae: Apiformes) Populations Assessed by Geometric Wing Morphometry

Abstract: We studied the differentiation of North American squash bee (Apidae: Apiformes) populations by using geometric wing morphometry to evaluate hypotheses for the origin and possible expansion route of bees after the dispersal of their Cucurbita floral hosts. Two hypotheses consider the possible impact of early human cultures on the distribution of this mutualistic species complex: 1) the geographic range of the bees naturally expanded after the hypsithermal range expansion of the wild buffalo gourd, Cucurbita foe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
4
9
0
2
Order By: Relevance
“…The correct assignment of almost 90% of the colonies to its original country is very promising for supporting measures for the conservation of these bees. Similar results of geographical traceability using geometric morphometrics of wings were also reported by Mendes et al (2007) Francisco et al (2008), and Bischoff et al (2009.…”
Section: Discussionsupporting
confidence: 87%
“…The correct assignment of almost 90% of the colonies to its original country is very promising for supporting measures for the conservation of these bees. Similar results of geographical traceability using geometric morphometrics of wings were also reported by Mendes et al (2007) Francisco et al (2008), and Bischoff et al (2009.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, the utilization of geometric morphometrics has increased in population (Tilde et al 2000, Francoy et al 2006, Nunes et al 2008, Nunes et al 2012, heritability (Monteiro et al 2002), evolutionary (Bonatti et al 2014) and reproductive (Carvalho et al 2011) studies of bees. These reports have shown that geometric morphometric data are effective in the identification of groups and lineages (Francoy et al 2008, Francoy et al 2009, Bischoff et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the geometric morphometrics of wings have been useful to establish the geographic origin of individuals of a single species (Bischoff et al 2009, Nunes et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the patterns of wing venation of bees from Mexico, Nicaragua, El Salvador, Guatemala and Costa Rica indicated marked differences among the populations, correctly re-assigning 87% of the individuals to the respective group . It was also demonstrated that it is valid for other examples, like bees from the genus Peponapis in North America (Bischoff et al, 2009), Apis florea (Kandemir et al, 2009) and Apis mellifera populations (Özkhan and Kandemir, 2010) and Nannotrigona testaceicornis sub-populations (Mendes et al, 2007). Another geometric approach that is very promising is the outline of wing cells.…”
Section: Morphometric Analysismentioning
confidence: 98%